A qualitative study of provider burnout: do medical scribes hinder or help?. Issue 3 (12th August 2021) - Corby, Sky; Ash, Joan S; Mohan, Vishnu; Becton, James; Solberg, Nicholas; Bergstrom, Robby; Orwoll, Benjamin; Hoekstra, Christopher; Gold, Jeffrey A
Abstract: Objective: Provider burnout is a crisis in healthcare and leads to medical errors, a decrease in patient satisfaction, and provider turnover. Many feel that the increased use of electronic health records contributes to the rate of burnout. To avoid provider burnout, many organizations are hiring medical scribes. The goal of this study was to identify relevant elements of the provider–scribe relationship (like decreasing documentation burden, extending providers' careers, and preventing retirement) and describe how and to what extent they may influence provider burnout. Materials and Methods: Qualitative methods were used to gain a broad view of the complex landscape surrounding scribes. Data were collected in 3 phases between late 2017 and early 2019. Data from 5 site visits, interviews with medical students who had experience as scribes, and discussions at an expert conference were analyzed utilizing an inductive approach. Results: A total of 184 transcripts were analyzed to identify patterns and themes related to provider burnout. Provider burnout leads to increased provider frustration and exhaustion. Providers reported that medical scribes improve provider job satisfaction and reduce burnout because they reduce the documentation burden. Medical scribes extend providers' careers and may prevent early retirement. Unfortunately, medical scribes themselves may experience similar forms of burnout. Conclusion: Our data from providers and managers suggest that medical scribes help to reduce provider burnout. However, scribes are not the only solution for reducing documentation burden and there may be potentially better options for preventing burnout. Interestingly, medical scribes sometimes suffer from burnout themselves, despite their temporary roles.